The Design and Performance of the MINERνA Experiment - Budd H.S. (2012)
This work was supported by the Fermi National Accelerator Laboratory, which is operated by the Fermi Research Alliance, LLC, under contract No. DE-AC02-07CH11359, including the MINERvA construction project, with the United States Department of Energy. Construction support also was granted by the United States National Science Foundation under NSF Award PHY-0619727 and by the University of Rochester. Support for participating scientists was provided by NSF and DOE (USA) by CAPES and CNPq (Brazil), by CoNaCyT (Mexico), by CONICYT (Chile), by CONCYTEC, DGI-PUCP and IDI-UNI (Peru), and by Latin American Center for Physics (CLAF). Additional support came from Jeffress Memorial Trust (MK), and Research Corporation (EM). Finally, we are grateful to the staff of Fermilab for their contributions to this effort.